EFEKTIFITAS PENERAPAN APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) DI DESA PADANGIN KECAMATAN MUARA HARUS KABUPATEN TABALONG (JAPB, 2022)
The SISKEUDES application is used for clean, orderly, effective, and efficient village financial management and realizing transparent, accountable, participatory village financial management. It is carried out in an orderly and budgetary discipline; in implementing SISKEUDES, the government has its obstacles. The purpose of this study was to determine and analyze the Effectiveness of the Implementation of the Village Financial System (SISKEUDES) in Padangin Village, Muara Must District, Tabalong Regency. This study uses qualitative research. The data collection methods used are interviews, observation, and documentation. The results of this study indicate that the effectiveness of the Village Financial System (SISKEUDES) application in Padangin Village, Muara Must District, Tabalong Regency is categorized as Effective. Keywords: Effectiveness, Siskeudes Application, Village Financial Management Process